2019
DOI: 10.1177/0002039719848506
|View full text |Cite
|
Sign up to set email alerts
|

Colonialism, Land, Ethnicity, and Class: Namibia after the Second National Land Conference

Abstract: Since independence in March 1990, the unequal distribution and ownership of land as a leftover of colonial-era dispossession and appropriation has been a major issue of sociopolitical contestation in Namibia. This article summarises the structural colonial legacy and the efforts made towards land reform. Reference points are the country’s first national land reform conference in 1991 and the second national land reform conference in October 2018. The analysis points to the contradictory factors at play, seekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Predators such as lions, wild dogs, and hyenas, among others, were seen by officials and settlers as threats to the socio-economic prospects of commercial farming (Heydinger 2020). Because of these apartheid era land policies, competing predator species were eradicated in central and southern Namibia, land that remains mostly private/freehold commercial land today (Melber 2019). Policies supporting the eradication of predators on settler farms, however, were prohibited in African communities that suffer the same financial and physical impacts of HWC.…”
Section: Methodsmentioning
confidence: 99%
“…Predators such as lions, wild dogs, and hyenas, among others, were seen by officials and settlers as threats to the socio-economic prospects of commercial farming (Heydinger 2020). Because of these apartheid era land policies, competing predator species were eradicated in central and southern Namibia, land that remains mostly private/freehold commercial land today (Melber 2019). Policies supporting the eradication of predators on settler farms, however, were prohibited in African communities that suffer the same financial and physical impacts of HWC.…”
Section: Methodsmentioning
confidence: 99%
“…In Namibia, this nexus between time and landscape is visible as national, regional and internal borders, and in the veterinary fence dividing communal land in the North from commercial land in the South, which is known as the 'Red Line' (Miescher 2012). It is also evidenced in colonial and postcolonial town planning and urbanization (Pendleton 1974;Simon 1986;Fumanti 2016), in land and farm demarcations, and in the persistently unequal and still racialised access to land and resources (Melber 2005(Melber , 2019. Time as Geography continues to leave traces on the Namibian landscape, as Brandt so eloquently shows in her work.…”
Section: Punctum 5 German-namibian Spectropoetics 12mentioning
confidence: 99%
“…Land reforms have stimulated the emergence of a multitude of actors representing the state, communities and individuals, as well as formal and informal institutions regulating the relationships between these actors. Anastasia [16], Henning [17], and Boone [18] has shown that access to land remains marked by tensions. They note that high rates of ethnicity have acted as a real brake on land reform as a consequence of agricultural growth in Africa.…”
Section: Mcda000662 7(3)2020mentioning
confidence: 99%